Fostamatinib for the Treatment of Hospitalized Adults With Coronavirus Disease 2019: A Randomized Trial. (28th August 2021) - Strich, Jeffrey R; Tian, Xin; Samour, Mohamed; King, Christopher S; Shlobin, Oksana; Reger, Robert; Cohen, Jonathan; Ahmad, Kareem; Brown, A Whitney; Khangoora, Vikramjit; Aryal, Shambhu; Migdady, Yazan; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) requiring hospitalization is characterized by robust antibody production, dysregulated immune response, and immunothrombosis. Fostamatinib is a novel spleen tyrosine kinase inhibitor that we hypothesize will ameliorate Fc activation and attenuate harmful effects of the anti-COVID-19 immune response. Methods: We conducted a double-blind, randomized, placebo-controlled trial in hospitalized adults requiring oxygen with COVID-19 where patients receiving standard of care were randomized to receive fostamatinib or placebo. The primary outcome was serious adverse events by day 29. Results: A total of 59 patients underwent randomization (30 to fostamatinib and 29 to placebo). Serious adverse events occurred in 10.5% of patients in the fostamatinib group compared with 22% in placebo ( P  = .2). Three deaths occurred by day 29, all receiving placebo. The mean change in ordinal score at day 15 was greater in the fostamatinib group (-3.6 ± 0.3 vs -2.6 ± 0.4, P  = .035) and the median length in the intensive care unit was 3 days in the fostamatinib group vs 7 days in placebo ( P  = .07). Differences in clinical improvement were most evident in patients with severe or critical disease (median days on oxygen, 10 vs 28, P  = .027). There were trends toward more rapid reductions in C-reactive protein, D-dimer, fibrinogen, and ferritin levels in the fostamatinib group. Conclusion: For COVID-19 requiring hospitalization, the addition of fostamatinib to standard of care was safe and patients were observed to have improved clinical outcomes compared with placebo. These results warrant further validation in larger confirmatory trials. Clinical Trials Registration: Clinicaltrials.gov, NCT04579393. Abstract : In this placebo-controlled, double-blind, randomized trial of adult patients on oxygen hospitalized with COVID-19, fostamatinib in addition to standard of care was safe and well-tolerated. Serious adverse events occurred in 10.5% of patients in fostamatinib compared with 22% in placebo.